Abnormalities of primary and secondary hemostasis in multiple myeloma: insights from studies on thrombopoiesis, the coagulation system, and the bone marrow microenvironment - Abdi, Jahan; Nasr, Payman (Frontiers in Hematology, 2025)
In multiple myeloma (MM), hemostatic disorders such as thrombocytopenia, coagulopathies, and thrombophilia are well-documented. These abnormalities can be partially attributed to therapy, including thrombocytopenia following treatment with proteasome inhibitors such as bortezomib and carfilzomib or thrombosis associated with immunomodulatory drugs such as thalidomide and lenalidomide. However, acquired hemostatic disorders have also been observed in untreated or newly diagnosed MM patients. This review explores these abnormalities in both treated and untreated contexts, presenting recent studies that provide new insights into the mechanisms underlying these complications. It highlights the role of the bone marrow microenvironment, particularly mesenchymal stromal cells (MSCs) and extracellular vesicles (EVs). Additionally, the review discusses future research directions on hemostatic disorders, including bleeding and thrombosis, in MM patients. Overall, this review aims to be a valuable resource for scientists and clinicians in the field.